2021
DOI: 10.1186/s41182-021-00368-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carbapenemase-producing Klebsiella pneumoniae at a tertiary care hospital in Kathmandu, Nepal

Abstract: Aim Although carbapenem is the last-resort drug for treating drug-resistant Gram-negative bacterial infections, prevalence of carbapenem-resistant bacteria has substantially increased worldwide owing to irrational use of antibiotics particularly in developing countries like Nepal.  Therefore, this study was aimed to determine the prevalence of carbapenemase-producing K. pneumoniae and to detect the carbapenemase genes (blaNDM-2 and blaOXA-48) in at a tertiary care hospital in Nepal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
3
3
3
Order By: Relevance
“…About one-third and nearly two-thirds of the GNB showing resistance to meropenem had positive phenotypes by MHT and CDT or DDST, respectively. Similar findings were reported elsewhere, that MHT has low sensitivity and specificity rates, failing to detect MBLs producing GNB [24] and also that the high proportion of MBLs detection by CDT and DDST may be due to the good dissemination and predominance of genes encoding for MBLs locally and globally [14,[25][26][27].…”
Section: Discussionsupporting
confidence: 87%
“…About one-third and nearly two-thirds of the GNB showing resistance to meropenem had positive phenotypes by MHT and CDT or DDST, respectively. Similar findings were reported elsewhere, that MHT has low sensitivity and specificity rates, failing to detect MBLs producing GNB [24] and also that the high proportion of MBLs detection by CDT and DDST may be due to the good dissemination and predominance of genes encoding for MBLs locally and globally [14,[25][26][27].…”
Section: Discussionsupporting
confidence: 87%
“…These ndings are in agreement with Gurung et al report from Nepal [20]. Nevertheless, the frequency of carbapenemase production in this study was lower than in previous reports from India at 58.2% [31], Iran 43.3% [32], Malaysia 71.4% [33], and Nepal 51.1% [34]. Genotypic analysis in the current study revealed that the frequent gene among carbapenemase-producing isolates was bla OXA−48 (36.8%), but only 15.8% and 5.3% harbored the bla NDM and bla IMP genes, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence correlates to great extent with the studies by Nirwati et al, Gill et al, Farkhanda et al, Sodhi et al, Sonia et al and Odari et al who reported prevalence to be 17.36%, 22.43%, 15.18%, 21.23%, 23.73% and 15.7% respectively [17][18][19][20][21][22]. However, Pyakurel et al reported prevalence 31.4% which is higher than the present study 23. Maximum isolates of K. pneumoniae were obtained from urine (30.24%), followed by ET tubes/ET secretions (27.82%), other respiratory samples (13.30%), blood (12.90%) pus and wound swabs (11.29%) and minimum from body fluids (4.43%).…”
supporting
confidence: 71%
“…Gupta et al, Pyakurel et al and Su et al have reported isolation rate of K. pneumoniae 70%, 55.1% and 20.6% from ICU samples respectively. 23,29,31 In the present study the pattern of resistance shown by K. pneumoniae towards various antimicrobials was reported as following amoxicillin/clavulanic acid (90.7%), imipenem (78.3%), meropenem (78.7%), ceftiaxone (95.5%), ciprofloxacin (89.6%), amoxicillin/clavulanic acid (90.7%), cotrimoxazole (85.1%), however isolates were highly sensitive to colistin (95.6%) followed by amikacin (76.7%) and tigecycline (63.7%). 31,[39][40][41] Hoang et al had reported 95% MBL production in K. pneumoniae isolates, which is quite higher as compared to this study.…”
Section: Mbl Production In K Pneumoniaementioning
confidence: 99%